Perkembangan Taman Bacaan di Kota Makassar - Irsan, Irsan (Program Studi Ilmu Perpustakaan UIN Alauddin, 2014)
The term âreading gardenâ refers to a dynamic and creative conceptual on reading place. The development of reading garden in Makassar city began since the beginning of 2000. There were three kinds of reading gardens; reading gardens built by the government, reading gardens established by social communities, and reading gardens maintained by individuals. The one that was built by the government increased in numbers since the government launched GMGM (Gerakan Makassar Gemar Membaca) or Makassar Love Reading Program. The presence of TBK (Reading Gardens built by the Government) is just about place for reading, the ratio between the total of reading gardens and Makassar population is not balanced. Meanwhile, the one that was established by the community is flexible, dynamic, creative, and variety in services. On the other hand, reading gardens maintained by individuals are much more flexible in which they have participated in many actions in societies. The presence of three kinds of reading gardens in Makassar city is expected to encourage the citizen to love reading.Taman bacaan, Perpustakaan komunitas